2004
DOI: 10.1163/156853904772746628
|View full text |Cite
|
Sign up to set email alerts
|

Chickadee Song Structure is Individually Distinctive Over Long Broadcast Distances

Abstract: SummaryThe two-note fee-bee song of male black-capped chickadees functions during the dawn chorus, in part, as a sexual signal across large distances. How song structure might encode information about male quality, however, remains unclear.We studied the availability of cues to male social rank (a proxy indicator of male quality), within the acoustic structure of dawn chorus songs of male chickadees whose ock dominance status we determined the previous winter. We used analysis of variance and discriminant func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…The ratio CV b / CV w was then calculated to obtain a measure of relative between-male variability for each boatwhistle feature. When this ratio is larger than one, it suggests that the acoustic parameter is more variable between individuals relative to its variability within individuals and could be used as a cue for individual discrimination (Christie et al 2004). KruskalWallis tests were computed to compare differences among males for each acoustic feature in the two time frames.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio CV b / CV w was then calculated to obtain a measure of relative between-male variability for each boatwhistle feature. When this ratio is larger than one, it suggests that the acoustic parameter is more variable between individuals relative to its variability within individuals and could be used as a cue for individual discrimination (Christie et al 2004). KruskalWallis tests were computed to compare differences among males for each acoustic feature in the two time frames.…”
Section: Discussionmentioning
confidence: 99%
“…However, in highly reverberant habitats, such as those frequented by black-capped chickadees (Smith, 1991), constructive and destructive interference can introduce fluctuations in frequency attenuation that confound interpretation of variations in the spectra of received songs. Using acoustic transmission studies, Fotheringham and Ratcliffe (1995) found that differential frequency attenuation in fee-bee songs did not reliably indicate source distance (however, see Christie et al, 2004a). Figure 2. (A) Spectral peaks are evident both from the directly received bee note and from the reverberant tail of the preceding fee note (feeR) after a song has traveled 80 m (FFT = 2048; 98% overlap; 250 ms Hanning window).…”
Section: Cues To Singer Distancementioning
confidence: 99%
“…bee), and this frequency relationship between the two notes remains relatively consistent across song bouts (Horn et al, 1992;Weisman et al, 1990). Fee-bee songs contain acoustic features indicating individual identity (Christie et al, 2004a;Hahn et al, 2013b), and field (Wilson & Mennill, 2010) and laboratory (Phillmore et al, 2002) studies have demonstrated that chickadees can discriminate among individuals based on their songs. Although the black-capped chickadees' range extends across most of North America (Smith, 1991), little geographical variation has been described in this song (although, variation has been found in geographically isolated populations of chickadees, where some animals produce unusual songs; see Gammon & Baker, 2004;Kroodsma et al, 1999).…”
mentioning
confidence: 93%